Abstinent patients with alcohol use disorders show an altered plasma cytokine profile: Identification of both interleukin 6 and interleukin 17A as potential biomarkers of consumption and comorbid liver and pancreatic diseases. (November 2020) - García-Marchena, Nuria; Maza-Quiroga, Rosa; Serrano, Antonia; Barrios, Vicente; Requena-Ocaña, Nerea; Suárez, Juan; Chowen, Julie Ann; Argente, Jesús; Rubio, Gabriel; Torrens, Marta; López-Gallardo, Meritxell; Marco, Eva María; et al.
Background: Recent studies have demonstrated that alcohol consumption can modulate the immune system by directly activating natural immunity and triggering inflammatory processes in the central nervous system and in peripheral organs, such as the liver and pancreas. Patients with alcohol use disorders have an elevated frequency of comorbid mental disorders and gut diseases (i.e. fatty liver and pancreatitis) that complicate diagnosis, treatment and prognosis. Aims: The present study aims to explore possible associations in circulating plasma cytokine concentrations in abstinent patients diagnosed with alcohol use disorders. Methods: To this end, 85 abstinent subjects with alcohol use disorders from an outpatient setting and 55 healthy subjects were evaluated for both substance and mental disorders. The plasma levels of cytokines interleukin 1 beta, interleukin 4, interleukin 6, interleukin 17A, interferon gamma and tumour necrosis alpha were determined and their association with (a) history of alcohol consumption, (b) psychiatric comorbidity and (c) liver/pancreas comorbidities was explored. Results: We found that plasma concentrations of interleukin 1 beta, interleukin 6 and tumour necrosis alpha were increased, whereas plasma concentrations of interleukin 4, interleukin 17A and interferon gamma were decreased in abstinent alcohol use disorder patients as compared with control subjects. Moreover, we found that changes in interleukin 6 and interleukin 17A plasma concentrations in alcohol use disorder patients were associated with the presence of liver and pancreatic diseases. Conclusion: The present results suggest alcohol use disorder is associated with alterations of plasma cytokines, being interleukin 6 and interleukin 17A potential biomarkers of the presence of comorbidities of digestive organs. The clinical relevance of these findings is discussed in the context of alcohol-induced inflammatory processes.